2017
DOI: 10.21873/anticanres.12083
|View full text |Cite
|
Sign up to set email alerts
|

Orlistat Reduces Proliferation and Enhances Apoptosis in Human Pancreatic Cancer Cells (PANC-1)

Abstract: This study showed, to our knowledge for the first time, that orlistat exhibits significant antitumor activity against PANC-1 cells. This implies that orlistat analogs with good oral bioavailability may find application in pharmacotherapy of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Most importantly, some inhibitors show selective activity against CSCs rather than bulk tumor cells. Strikingly, Orlistat, a FDA-approved anti-obesity drug targeting FASN, exerts a potent anti-tumor activity in various cancers [ 201 , 202 ]. Remarkably, inhibition of FASN by Orlistat in EGFR mutated NSCLC suppresses tumor growth in vitro and in vivo through reducing EGFR palmitoylation but inducing mutant EGFR ubiquitination and subsequent proteasomal degradation [ 203 ].…”
Section: Targeting Lipid Metabolism As Novel Therapeutic Strategies Amentioning
confidence: 99%
“…Most importantly, some inhibitors show selective activity against CSCs rather than bulk tumor cells. Strikingly, Orlistat, a FDA-approved anti-obesity drug targeting FASN, exerts a potent anti-tumor activity in various cancers [ 201 , 202 ]. Remarkably, inhibition of FASN by Orlistat in EGFR mutated NSCLC suppresses tumor growth in vitro and in vivo through reducing EGFR palmitoylation but inducing mutant EGFR ubiquitination and subsequent proteasomal degradation [ 203 ].…”
Section: Targeting Lipid Metabolism As Novel Therapeutic Strategies Amentioning
confidence: 99%
“…Orlistat contains a highly reactive beta-lactone that covalently captures reactive serine residues such as Ser2308 within the TE domain of FASN [ 119 ]. Its anti-tumor properties have been explored extensively where studies have shown shrinkage in tumors both in vitro and in vivo [ 75 , 89 ]. However, Orlistat is highly unstable due to the presence of beta-lactone, has poor water solubility and poor gastrointestinal absorption that hinders its advancement in clinical trials [ 120 ].…”
Section: Targeting Fasn In Cancermentioning
confidence: 99%
“…TVB-2640 has entered clinical trials, e.g., for people with resectable colon cancer (phase 1), for advanced breast cancer (phase 2), or for high grade astrocytoma (phase 2). Orlistat is a US food and Drug Administration (FDA)-approved anti-obesity drug, and it has been shown that orlistat reduces human pancreatic cancer cell growth [ 14 , 95 ]. As orlistat has low oral bioavailability which may reduce cancer therapy effect [ 7 ], several studies suggest combination therapies with ALCAR (AMPK activator) for prostate cancer [ 96 ], or simultaneous targeting glycolysis, glutaminolysis, and FA synthesis by lonidamine, 6-diazo-5-oxo- l -norleucine which are combined with orlistat for colon cancer therapy [ 97 ].…”
Section: Targeting Lipid Metabolism and Therapy Options For Cancermentioning
confidence: 99%